Indonesian Language Learning In Elementary School: Building Gender Awareness For 3rd Grade Students - Dinaryanti, Dina; Apriliya, Seni; Nursofa, Risma; Rahmi, Hestika Asri; Nugraha, Mia Uswa; Purnamawati, Eva (Indonesian Journal of Primary Education, 2024)
This research was conducted to provide insight into gender awareness in education. Particularly in the context of Indonesian language learning in primary schools. Through investigating the perspectives of parents, teachers and students as well as the practice of learning Indonesian in the classroom using non-discriminatory materials and learning environments without gender boundaries, this research seeks to contribute to building a more inclusive gender awareness in the educational environment. Survey, interview and observation methods of parents, teachers and grade 3 students were used to provide a comprehensive view of the understanding of gender awareness. The results show that although there is support for the concept of gender equality, parents' and teachers' understanding is still limited. Teachers do not fully understand the importance of gender awareness in learning. This issue is seen as not affecting inclusive learning. In fact, gender awareness is one part of it and teachers have a major role in building this perspective. Synergy is needed to improve parents', teachers' and students' understanding of gender issues in education. Teacher training and professional development, integration of gender equality values in the curriculum, and inclusive education for students can be the next steps to strengthen gender equality in education. Thus, this research provides new insights and contributions to advance gender awareness as a form of creating an inclusive learning environment, especially in primary schools.